Mechanism of Potentiation by Manganese Ion of Aggregation of Porcine Pancreatic Elastase-Treated Human Platelets - Azuma, Hiroyuki; Shigekiyo, Toshio; Miura, Shinji; Uno, Yuka; Saito, Shiro (Thrombosis and Haemostasis, 1989)
The effect of manganese ion (Mn2+) on the aggregation of porcine pancreatic elastase-treated platelets (ETP) induced by fibrinogen (Fbg) was studied. Mn2+ enhanced the aggregation of ETP on addition of Fbg specifically and dose-dependently. This effect of Mn2+ was not associated with the formation of thromboxane A2, and was not affected by pretreatment of ETP with acetylsalicylic acid in the presence of Mn2+. Moreover, it was not dependent on extracellular adenosine diphosphate, as shown by removal of extracellular adenosine diphosphate by pretreatment of ETP with creatine phosphate/creatine phosphokinase. Studies on the binding of 125I-Fbg to ETP showed that Mn2+ increased the Kd value of binding but did not affect the number of Fbg binding sites. These results indicate that Mn2+ specifically and dose-dependently potentiated Fbg-induced aggregation of ETP and that this effect of Mn2+ may be due to an increase in the affinity of binding of Fbg to the glycoprotein IIb-IIIa complex on the membranes of ETP.
Keywords: Manganese; Porcine pancreatic elastase-treated platelets; Fibrinogen; Glycoprotein IIb-IIIa